URGENSI DAN MEKANISME VALIDASI BUKTI ELEKTRONIK DALAM PEMBUKTIAN PERADILAN ELEKTRONIK - Endri (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2021)
This research is trying to explain two legal issues in relation to the submission of electronic evidence in e- Litigation evidence system, those are about the urgency of electronic evidence validation in proving a case and how the ideal mechanism of electronic evidence validation at the e-Litigation proof stage is. The discourse of the trial by fully using E-Court which includes the proof stage in it has not yet been implemented due to various obstacles, including regulations, availability of supporting facilities and Human Resources (HR). It is important to study this legal issue in order to optimize E-Court so that judicial modernization with information technology approach can be quicklyimplemented, solely to realize the vision of the Supreme Court and ensure better access to justice in the future. The results of this research conclude that the electronic evidence validation process in E- Litigation is a vital stage that cannot be ruled out in order to determine the validity of an electronic evidence and how important digital forensic procedures in the electronic evidence validation process.